Current issues in syntactic cartography a crosslinguistic perspective - Si, Fuzhen; Rizzi, Luigi, 1952- (Linguistik aktuell ;, 2021)
"This book illustrates recent developments in cartographic studies, seen from a comparative perspective. The different chapters explore various aspects of theoretical and descriptive syntax, bearing on such topics as selection, causativity, binding, light verb constructions, the structure of the high and low peripheral zones. Syntactic issues in the study of dialects and ancient languages are also addressed. The languages investigated include French, Hebrew, Standard Dutch and the Ghent dialect, Etruscan, Japanese, English, Arabic, Mandarin Chinese and the Teochew dialect. The intended readers of this book include researchers and students working on natural language syntax, the interface between syntax and semantics/pragmatics, and comparative and typological linguistics, as well as scholars interested in particular languages such as East Asian and Romance languages"--